Kerjasama Internasional Indonesia: Memperkuat Keamanan Nasional di Bidang Keamanan Siber: Indonesia’s International Cooperation: Strengthening National Security in the Field of Cyber Security - Afifah Fidina Rosy (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2020)
This research analyses the development of cyber security capacity and international cooperation in cyber security carried out by Indonesia with other countries. Research results show that the development of Indonesian cyber security has been strengthened by the establishment of National Cyber and Crypto Agency. It is also found that Indonesian cyber diplomacies have yielded cooperation with other countries to strengthen cyber security as part of national security. They have been carried out bilaterally or multilaterally, and can be categorized as cooperative security based on common goals, i.e. to prevent the rise of threats to national security. Keywords: cyber security, cyber crime, security, internet, cooperative security, cooperation.